Gibbs free energy and Helmholtz free energy for a three-dimensional Ising-like model - Kozlovskii, M.P.; Romanik, R.V. (Condensed Matter Physics, 2011)
The critical behavior of a 3D Ising-like system is studied at the microscopic level of consideration. The free energy of ordering is calculated analytically as an explicit function of temperature, an external field and the initial parameters of the model. Within a unified approach, both Gibbs and Helmholtz free energies are obtained and the dependencies of them on the external field and the order parameter, respectively, are presented graphically. The regions of stability, metastability, and unstability are established on the order parameter--temperature plane. The way of implementation of the well-known Maxwell construction is proposed at microscopic level. В данiй роботi на мiкроскопiчному рiвнi розгляду вивчається критична поведiнка тривимiрної iзiнго-подiбної системи. Аналiтично обчислюється вiльна енергiя впорядкування як функцiя температури, зовнiшнього поля i початкових параметрiв моделi. В межах запропонованого пiдходу отримано ви-рази для вiльної енергiї Гiббса i Гельмгольца, їх залежностi вiд поля i параметра порядку приведенi також графiчно. На площинi параметр порядку–температура знайденi областi стабiльностi, метаста-бiльностi та нестабiльностi. Запропоновано спосiб реалiзацiї правила Максвелла на мiкроскопiчно-му рiвнi.